Structural and psychological empowerment of students obtaining continuing leadership education in Finland–a national survey. (September 2022) - Terkamo-Moisio, Anja; Palonen, Mira; Vaartio-Rajalin, Heli; Peltonen, Laura-Maria; Partanen, Pirjo; Leino-Kilpi, Helena; Kaunonen, Marja; Kaakinen, Pirjo; Häggman-Laitila, Arja
Abstract: Background: In nursing, empowerment may be deemed one's potential to gain power, achieve goals and promote one's skills to advance positive changes in the working environment, or decentralization of authority. Empowerment is associated with nurses' and nurse leaders' satisfaction, performance and organizational commitment, as well as burnout, emotional exhaustion and intentions to leave the profession. Research on nurse empowerment in relation to continuing education is sparse. Objectives: This study describes the structural and psychological empowerment levels of students beginning a collaboratively implemented continuing leadership education program. Design: Cross-sectional electronic survey. Settings: National, continuing nursing leadership education program (37 ECT) organized by five universities that provide masters level education to nurse leaders in Finland. Participants: Students ( N = 85) working at nine healthcare organizations across the service system as current or prospective nurse leaders and enrolled in the continuing leadership education program. Methods: The Conditions of Work Effectiveness Questionnaire and the Work Empowerment Questionnaire were each used to measure structural and psychological empowerment, respectively. The data were collected between October 2019 and February 2020. Results: A total of 69 students participated (response rate 81 %). Moderate levels of both structural and psychological empowerment were observed. In structural empowerment, the strongest dimension was access to opportunity (4.1, SD 0.7), whereas access to support was the weakest (2.7, SD 0.7). The strongest psychological empowerment dimension was verbal empowerment (8.5, SD 1.9) and the weakest was outcome empowerment (7.0, SD 1.6). Conclusions: Nurses and nurse leaders seem to lack the status and power required to impact their organizations, possibly causing them to apply for nursing leadership education. Nurse leaders should be given opportunities for continuing leadership education to improve empowerment and, as a result, staff outcomes.